The Role of The Department of Culture and Tourism of Rokan Hulu District in The Development of The Aek Metertu Waterfall Tourism Object - Data Wardana; Ayu Rahayu Lubis (UIR Press, 2023)
This research is to look at the role of the Culture and Tourism Office of Rokan Hulu Regency in developing the Aek Martua Waterfall tourist object which is one of the tourist destinations in Rokan Hulu Regency. This study uses a descriptive research type with a qualitative approach by observing, interviewing and documenting field data. The results of the research show that it is necessary to make development efforts to increase tourist attractiveness by making events, building facilities and infrastructure to facilitate access to tourist sites and community support so that development still pays attention to local wisdom. The obstacle in the development is the distance to the location with the condition of the road passing through the Barisan Hill. The Rokan Hulu Regency Government is expected to be able to carry out developments which are outlined in the form of programs and activities at the Aek Martua tourist attraction.